Odpowiedź :
Odpowiedź:
16)
1) 7/4 × 8/7 - 3 ÷ 9/2 = 2 - 3 × 2/9 = 2 - 2/3 = 1 1/3
2) 12/7 × (11/4 - 5/3 × 1/4) = 12/7 × (11/4 - 5/12) =
= 12/7 × (33/12 - 5/12) = 12/7 × 28/12 = 28/7 = 4
3) 10/3 × (9/4 - 3/2 × 1/5) = 10/3 × (9/4 - 3/10) =
= 10/3 × (45/20 - 6/20) = 10/3 × 39/20 = 390/60 = 39/6 = 13/2 = 6,5
4)
[tex] \frac{ \frac{13}{4} + \frac{2}{4} }{ \frac{10}{3} \times ( \frac{11}{6} - \frac{13}{12} ) } [/tex]
[tex] \frac{ \frac{15}{4} }{ \frac{10}{3} \times (\frac{22}{12} - \frac{13}{12}) } [/tex]
[tex] \frac{ \frac{15}{4} }{ \frac{10}{3} \times \frac{9}{12} } [/tex]
[tex] \frac{ \frac{15}{4} }{ \frac{10}{3} \times \frac{3}{4} } [/tex]
[tex] \frac{ \frac{15}{4} }{ \frac{10}{4} } [/tex]
[tex] \frac{15}{4} \times \frac{4}{10} [/tex]
= 15/10 = 3/2 = 1,5